PRESERVING TRADITION: THE ADAT LAW SYSTEM OF THE BADUY COMMUNITY AND ITS CONSTITUTIONAL RELEVANCE - Sodikin, Sodikin; Maranjaya, Abdul Kahar (Universitas Syiah Kuala, 2025)
The Baduy adat law community is a distinct group that operates within a socio-cultural framework deeply rooted in their traditions. Central to this framework is the adat institution, which serves as the foundation for their governance system. In the Kanekes adat village, the structure and role of the adat institution reflect an adat state system that is derived from the values of their ancestors, known as Karuhun, and is consistent with the principles of Indonesian constitutional law. This study employs a juridical normative methodology to examine and analyze the conditions of the Kanekes Adat Village from a constitutional perspective. The findings reveal that the Baduy adat law community possesses characteristics that have sustained their adat institutions for thousands of years. They adhere to the norms of the Sunda Wiwitan religion, emphasizing the importance of upholding the values of the Karuhun, which serve as guiding principles (Pikukuh) that must be followed. The governance system they adopt is characterized as an adat state law system, which democratically distributes authority among various institutions. The apex of power and leadership resides with the Puun, who plays a crucial role in maintaining the community's traditions and governance. This structure not only reflects the community's commitment to their cultural heritage but also contributes to the broader framework of adat constitutional law in Indonesia, ensuring its relevance for future generations.